An introduction to molecular replacement - Evans, Philip (International Union of Crystallography, 2008)
Molecular replacement is fundamentally a simple trial-and-error method of solving crystal structures when a suitable related model is available. The underlying simplicity of the method is often obscured by the mathematical trickery required to make the searches computationally tractable. This introduction sketches the essential issues in molecular replacement without going into technical details. General search strategies are discussed and the alternative Patterson and likelihood approaches are outlined.